Grammatical Adaptation of English Loanwords of Gaming Industry in the Russian Language (Proceedings of Southern Federal University. Philology, 2017)
Semen V. Gornostaev (Volgograd, Russian Federation)The article is devoted to the grammatical adaptation of borrowed from the English lexems in the sphere of the interactive entertainment industry.It has been given also other processes of development of language units of the thematic groups: phonetic, lexical, semantic. Nominations were taken by continuous sampling of periodicals (magazine «Gambling»), various Internet sources and lively conversation, presented on Internet forums. The subject of the analysis is one-component substantive derivative and nonderivative nomination. During the study the following results were obtained. 1. The leading features of grammatical adaptation of anglicisms in the sphere of the gaming industry are: a) the appearance of declinability, stabilization of generic relatedness (not only animated, but also inanimate nouns), b) expansion of the capacity of the diversion, which is manifested in the formation of word-forming nest of three types - nest-pairs, nest-bundles and nest-chains. 2. Derivative words included in their composition, may belong to different parts of speech (nouns and verbs) and formed by affix (suffixes and prefixing) and non-affix (abbriviation, clipping, adding) ways. 3. There are units in the language-recipient that have not undergone the process of grammatical adaptation: blotches and immutable acronyms.Key words: abbreviation, affix, grammar adaptation, borrowing, gaming industry, word-forming nests, addition, truncation.